Blood Sugar Monitoring: Multifunctional Wearable System that Integrates Sweat‐Based Sensing and Vital‐Sign Monitoring to Estimate Pre‐/Post‐Exercise Glucose Levels (Adv. Funct. Mater. 47/2018). (19th November 2018) - Hong, Yongseok Joseph; Lee, Hyunjae; Kim, Jaemin; Lee, Minha; Choi, Hyung Jin; Hyeon, Taeghwan; Kim, Dae‐Hyeong
Abstract : In article number1805754, Dae‐Hyeong Kim and co‐workers report a wearable smart band functioning as sweat‐based glucose sensing strip. The smart band is capable of monitoring sweat glucose levels as well as heart rate, blood oxygen saturation level, and physical activity.